Pengaruh Pesan Kampanye Public Relations #MulaiDariMejaRias terhadap Brand Image Avoskin di Instagram - Putri Aulia; Winda Dwi Astuti Zebua (Kajian Administrasi Publik dan ilmu Komunikasi, 2025)
After achieving success with the #LoveAvoskinLoveEarth initiative, Avoskin continues its efforts by launching a new eco-friendly campaign called #MulaiDariMejaRias. In this campaign, Avoskin invites skincare product users to be more careful in choosing care items, and to use appropriate products for simplicity and sustainability. Brand image plays a very important role in marketing its products. One way to build a positive view in the community is through campaign activities. This study aims to analyze the impact of the message from the #MulaiDariMejaRias campaign via Instagram @avoskinbeauty, assess Avoskin's Brand Image related to the campaign, and evaluate the influence of public relations messages in the #MulaiDariMejaRias campaign on Avoskin's Brand Image on Instagram. The theory applied in this study refers to Messages from Perloff (2017), Soemirat, Soleh & Ardianto (2018) regarding brand image variables. The approach used in this study is a quantitative approach with a survey method to 86 respondents of Instagram followers @avoskinbeauty, using a random sampling technique. The research results showed a 41% impact of the #MulaiDariMejaRias public relations campaign message on Avoskin's brand image on Instagram. Furthermore, the #MulaiDariMejaRias campaign message was emotionally and linguistically effective, and the campaign successfully improved brand image through audience attitudes.